Theoretical concepts of the law of civil servants - Jakub Stelina (Правоприменение)
The subject. The article examines the conceptual foundations of the legal status of civil servants in the legal systems of Europe and the United States.The purpose of the article is to confirm or disprove hypothesis that there are common concepts and models of the law of civil servants for different legal systems.The methodology of the study includes general scientific methods (analysis, synthesis, description) and the method of comparative law.The main results and scope of their application. It is determined that the body of persons working for the state is diversified. Within it, three main groups can be distinguished: the political corps, professional public servants (officers) and auxiliary (service) staff. The author postulates that various theoretical models of civil servants ' rights are closely related to the problem of their position in the legal system. The place in the legal system depends on whether the position of all persons employed in the public sphere is considered as generally public law, or whether the law of public servants is regulated by both administrative and labour law in different proportions depending on the legal system. At the present stage, there are also trends aimed at establishing some rules similar to those that regulate entrepreneurial activity in a free market in the sphere of public administration. The concept of the so-called new public administration is among the most important ideas of this kind.Conclusions. The author found that the existence of different models of public service in different legal systems does not exclude the definition of some general models of the law of public servants. The most important in that respect is their division according to the nature of employment of civil servants. In countries that have not undergone dramatic political transformation, the concept of the law of public servants as part of public law is commonly accepted – consequently, public servants are regarded as public officers, their employment having the nature of a service. Such a model of public servants law is generally encountered in countries of the Western Europe. The situation is more complicated in countries where there was a political system of “real socialism”, for example, in Poland. Since the 1970s yhe law of public servants is part of labour law there, public servants being, from the formal point of view, employees with whom employment relationships are concluded, mostly using the tool of the contract of employment. It is worthwhile to observe that no decision to restore earlier solutions was made after the political changes of the year 1989.